The Comparison of Preemptive Oral Tramadol, Gabapentin Tramadol and Parasetamol Tramadol Combination on the Efficacy of Postoperative Pain Control in Breast Reduction Surgery - Muge Can; Zehra Hatipoglu; Cengiz Eser; Yasemin Gunes (Çukurova Üniversitesi Tıp Fakültesi Dergisi, 2013)
Purpose: Application of tramadol by intravenous patient controlled analgesia (PCA) is a routine method for controlling postoperative pain in the breast reduction operations. It was aimed to compare the efficacy of preemptive oral gabapentin/tramadol and parasetamol/tramadol combination usage on the postoperatif tramadol consumption in patients undergoing breast reduction operation. Material and Methods: Our study was held on 54 patients (ASA I-III, aged between 18-65 yr) undergoing breast reduction operation. Patients randomly divided into three groups. Group I were received 600mg tablet gabapentin and 35mg drop tramadol one hour before the operation. Group II were received 500mg tablet parasetamol and 35mg drop tramadol one hour before the operation. Group III (Control group) were received 35mg drop tramadol one hour before the operation. 30 minutes before the end of operation, 1mg/kg i.v. tramadol and 10mg metoklopramid HCL three groups were administred. After the end of operation, three groups were started to receive tramadol infusion and intravenous patient controlled analgesia (PCA) application (300 mg diluated with 0,09% 100cc SF, 0,2 mg/kg PCA, 15 min locked in time). Peroperative SpO2, KH, SKB, DKB, extubation, disillusion, response time to the verbal stimuli, postoperative pain scores (VRS, VAS), total tramadol consumption, additional analgesic need and side effects (nausea and vomiting, diplopia, dizziness) were recorded and evaluated. Results: Peroperative SpO2, KH, SKB, DKB, extubation, disillusion, response time to the verbal stimuli, postoperative pain scores (VRS, VAS), total tramadol consumption, additional analgesic need and side effects of groups were similar to each other. Peroperative second hour DKB values and postoperative twelfth hour additional analgesic need of second group was found higher compared to other groups. There were no significantly differences in the groups except diplopia. It was found higher in favour of the first group. Conclusion: Application of tramadol/gabapentin, tramadol/parasetamol and low dose tramadol (35mg) in patients undergoing breast reduction operation did not affect intraoperative hemodinami. The tramadol combined with postoperatif HKA also does not cause any differences among postoperative pain scores, 24 hours total tramadol consumption and additional analgesia need except twelfth hour. It was concluded that the side effects in group applied gabapentin were similar except diplopia. [Cukurova Med J 2013; 38(3.000): 417-425]